Modified continuity equation using left ventricular outflow tract three‐dimensional imaging for aortic valve area estimation. Issue 7 (7th June 2017) - Pinto Teixeira, Pedro; Ramos, Ruben; Rio, Pedro; Moura Branco, Luísa; Portugal, Guilherme; Abreu, Ana; Galrinho, Ana; Marques, Hugo; Figueiredo, Luísa; Cruz Ferreira, Rui
Abstract : Purpose: Aortic valve area (AVA) is usually estimated by the continuity equation (CE) in which the left ventricular outflow tract (LVOT) area is calculated assuming a circular shape. This study aimed to compare measurements of LVOT area using standard 2D transthoracic echocardiography (2DTTE), 3D transesophageal echocardiography (3DTEE), and multidetector computed tomography (MDCT) and assess their relative impact on AVA estimated by the CE. Methods and Results: We prospectively enrolled 60 patients with severe aortic stenosis (AS) referred for transcatheter aortic valve replacement (TAVR) who systematically underwent 2DTTE, 3DTEE, and MDCT. Mean LVOT areas obtained by 2DTTE (3.28±0.66 cm 2 ) and 3DTEE (3.95±0.90 cm 2 ) were significantly underestimated when compared to the mean MDCT LVOT area (4.31±0.99 cm 2 ). LVOT was rather elliptical than round, with a mean eccentricity index of 1.47 (ratio of maximum to minimum LVOT diameters) assessed by MDCT. Mean TTE AVA estimated by the CE was 0.62±0.20 cm 2 . Substitution of 2DTTE LVOT area by 3DTEE LVOT area in the CE resulted in AVA of 0.74±0.24 cm 2, while using MDCT LVOT area held an AVA of 0.80±0.24 cm 2 . MDCT‐derived AVA was similar to MDCT planimetric AVA and allowed 24% of patients to be reclassified from severe to moderate AS. Conclusions: 2DTTE and 3DTEE underestimate LVOT area when compared to MDCT with significant impact on AVA estimation. Assessment through MDCT fusion AVA may be of incremental value in patients with discrepant severity criteria for AS.